Respons Tanaman Mentimun Jepang terhadap Pemberian Asam Humat dan Pupuk NPK di Tanah Podsolik Merah Kuning - Wijaya, Melda Putri Lianti Andrian; Sasli, Iwan; Ruliyansyah, Agus (Perkebunan dan Lahan Tropika, 2026)
Japanese cucumber (Cucumis sativus L. var. Japanese) is a type of vegetable from the Cucurbitaceae family or gourd family. There are several types of cucumbers, one of which is the Japanese cucumber (kyuri), which is longer than regular cucumbers, has a slender fruit shape, soft flesh, smooth skin, and a greener color. The limited agricultural land results in the use of suboptimal land, which poses problems for nutrient availability, such as podsolic reddish-yellow soil (PMK). This study aims to determine the effect of the interaction between humic acid and NPK fertilizer on the growth and yield of Japanese cucumber plants in Reddish-Yellow Podsolic soil (PMK). The research was conducted in Kasromego Village, Beduai sub-district, Sanggau District, from June to September 2024. The design used was a Completely Randomized Design (CRD) split plot with 2 factors. The first factor is humic acid, which consists of 2 levels: H0 = without humic acid and H1 = with the addition of humic acid. The second factor is NPK fertilizer, with 3 levels: P1 = 6 g/plant, P2 = 12 g/plant, P3 = 18 g/plant. Research results show a significant interaction between humic acid and NPK fertilizer on fruit weight per plant and fruit length. The best combination is achieved with the application of humic acid and NPK fertilizer at a dose of 12 g/plant, resulting in the highest fruit weight and length.